Postcementation Hypersensitivity: Scientific Data Versus Dentists’ Perceptions - Stephen F. Rosenstiel, BDS, MSD,1 and Robert G. Rashid, DDS, MAS2 (Journal of Prosthodontics, 2003)
The purpose of this article was to obtain dentists’ opinions via an Internet survey as to the prevalence, causes, and prevention of postcementation sensitivity and compare their responses with published data on the problem.